Evaluación del efecto de la intensidad de labranza en la formación de costra superficial de un oxisol de sabana en los Llanos Orientales de Colombia : I. Caracterización química y textural en superficie - Galvis, JH; Amézquita Collazos, Edgar; Madero, E (2007)
A field trial was conducted to evaluate the cumulative effects of fertilization and tilling on corn crop and introduced pasture under no grazing. Changes in soil physical and chemical parameters were evaluated in the first centimeter depth of top soil of field plots that were established in 1995 in Matazul farm located at the east of Puerto Lopez, Meta, Colombia. After eight years of establishment, results showed that corn system significantly improved soil fertility of savanna but soil stabilizer parameters such as organic matter, organic Fe and fine silt were negatively affected. These effects were more pronounced with harrowing intensity. The system of improved pastures significantly increased soil organic matter and pH but with a tendency to decrease with tilling. These results point out the need for improved pasture phase in the rotation for sustainable land management and agricultural productivity.